Prototype Sistem Pendeteksi Kebocoran Gas Di Dapur Sebagai Upaya Pecegahan Kebakaran - Bayu Kusumo; Muhammad Husein (JURNAL ELEKTRO, 2025)
Prevention of fires caused by gas leaks is one of the top priorities in maintaining environmental safety. in domestic life. Errors in installation and slow handling when LPG gas leaks can trigger fires, so this study introduces a prototype gas leak detection system that is specifically designed as an effort to prevent fires.The design of this system integrates the Arduino Uno with the MQ-6 sensor to detect the presence of harmful gases such as methane and iso butane that can trigger a fire. The Arduino Uno serves as the main control unit that processes data from the MQ-6 sensor, which measures gas concentrations in real-time. When the MQ-6 sensor detects gas levels that exceed a predetermined threshold of < 200 ppm, the Arduino Uno activates warning mechanisms, including audible alarms and SMS notifications, to notify the user of the leak. In addition, this system is connected with an automatic exhaust fan device as an additional step to reduce the risk of fire. Testing of the system showed that the prototype was able to detect gas leaks with high accuracy and provide a timely response, thus contributing significantly to fire prevention efforts and improving safety. With the reliability and efficiency offered, this prototype offers an innovative solution to prevent the risk of fire in the home